PSYCHOSEMANTIC FEATURES OF THE «EGO»-SYSTEM IN PERSONS WITH DIFFERENT LEVELS OF EMOTIONAL MATURITY - Півень, Маргарита Анатоліївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article is devoted to the study of the psychosemantic features of the «Ego»-system in persons with different levels of emotional maturity. It is demonstrated that the emotional maturity of personality is a manifestation of the general personal maturity at different levels, one of which is the level of psycho-semantic features of the «Ego» -system. The peculiarities of the functioning of the «Ego»-system of persons with high and low levels of emotional maturity are considered – the «Ego»-syntonic and «Ego»-dystonic regions of the correlation network are represented in both groups, which have signifiant substantial differences. Emotionally mature personality is included into the main areas of realization, which are connoted by positive emotions.